Mediation of area and edge effects by adjacent land use - Hatfield,J; Barlow,J; Joly,CA; Lees,AC; Parruco,CF; Tobias,J; Orme,C; Banks-Leite,C (Conservation Biology, 2020)
Habitat loss, fragmentation and degradation have pervasive detrimental effects on tropical forest biodiversity, but the role of the surrounding land use (i.e. matrix) in determining the severity of these impacts remains poorly understood. We surveyed bird species across an interior-edge-matrix gradient to assess the effects of matrix type on biodiversity at 49 different sites with varying levels of landscape fragmentation in the Brazilian Atlantic Forest – a highly threatened biodiversity hotspot. Our findings revealed that both area and edge effects are more pronounced in forest patches bordering pasture matrix, while patches bordering Eucalyptus plantation maintained compositionally similar bird communities between the edge and the interior, in addition to exhibiting reduced effects of patch size. These results suggest that the type of matrix in which forest fragments are situated can explain a substantial amount of the widely-reported variability in biodiversity responses to forest loss and fragmentation.